VISITOR PERCEPTIONS OF RECREATION SPORTS FACILITIES AND INFRASTRUCTURE AS WELL AS MOTIVATION IN SPORTS IN THE SPORTS AREA OF HAJI AGUS SALIM PADANG - PRIMA NOFRI ANDIKA; Arif Fadhli Mukhlis; Endang Sepdanius (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
ABSTRACT This study aims to describe and analyze how visitors' perceptions of recreational sports facilities and facilities in the GOR Haji Agus Salim area and with existing conditions, what motivates visitors to do recreational sports in the GOR Haji Agus Salim area. The research method used is qualitative research. Techniques for collecting data on observations, interviews and documentation. The data validity technique uses data triangulation techniques. The results of the study show that visitors' perceptions of recreational sports facilities and infrastructure in the region of the Haji Agus Salim Sports Hall are in the sufficient category. The reason: with various obstacles surrounding recreational sports facilities and infrastructure in the GOR area, Haji Agus Salim, visitors are still busy visiting this sports area. With the existing situation and conditions, there are two things that motivate visitors to do recreational sports in the Haji Agus Salim Sports Area, namely: intrinsic motivation and intrinsic motivation. Instrinsic Motivation that the researchers found was: as a time for refresing the body from the busyness of activities, maintaining health and fitness and filling spare time with useful things). Whereas, extrinsic motivation is based on the findings of researchers, namely: an arena for social interaction and secondary socialization with friends and the people of Padang City, recommendations and invitations from friends or sports teachers, the beauty of Haji Agus Salim Sports Hall and places around it, and compared to other places in the GOR area Haji Agus Salim is an affordable gym for all people. Key words: perceptions, facilities and infrastructure, motivation, recreational sports